THE ORGANIZATION OF VOWEL SOUNDS IN LANGUAGE ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article provides a comprehensive overview of the classification of vowel sounds, detailing the key features used to categorize them, such as tongue height, backness, lip rounding, tension, and length. It explains the distinction between monophthongs and diphthongs, as well as the use of the International Phonetic Alphabet (IPA) to transcribe vowel sounds accurately across languages. The article highlights the diversity of vowel systems in different languages, from English's extensive inventory to the simpler vowel systems of languages like Spanish. It emphasizes the significance of vowel classification in fields like linguistics, language learning, and speech therapy, offering insight into how vowel sounds shape both speech production and language understanding. This resource is essential for anyone studying phonetics, phonology, or applied linguistics.